Image Steganography-Hiding Data within Image - Deshmukh, Esha; Dangle, Juily; Ghadi, Sagar; Kewat, Shailesh; Shewale, Kalpana (International Journal of Computer Sciences and Engineering, 2025)
Security of the data is of foremost important in today’s world. Security has become a main important field in information and communication technology. For highly secure, hidden communication and sharing of information steganography is used. Steganography is a method of hiding the existence of communication, by hiding information data in other carriers. Different carrier mediums can be used for this, but digital images are the most famous because of their frequent use on the internet. There are several techniques of steganography, among them some are too complicated than others. Every technique have their strong and weak parameters. LSB, DES and AES algorithm is been used in this project. LSB technique is simple, high payload, low complexity and easy to detect. AES and DES are the complex technique but provide high security. The execution time of LSB is more, DES moderate and AES takes less time. Using these three methods we are going to design our project. This will enhance the security of the data which is being transferred.